2002
DOI: 10.1021/ie020362a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Pore-Size Distribution of Lime on the Reactivity for the Removal of SO2 in the Presence of High-Concentration CO2 at High Temperature

Abstract: To develop a SO 2 sorbent that is highly reactive in the presence of high concentrations of CO 2 at high temperature, the effect of the pore-size distribution on the reactivity was investigated at 800°C using a natural limestone, natural lime, modified macroporous lime, and limestone. The modified lime samples were prepared from a kind of natural lime by water-acetic acid swelling and water swelling methods. The modified limestone was prepared from the modified lime by carbonation. Pores smaller than ca. 200 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
1
34
0
1
Order By: Relevance
“…The second one was slower and it can be controlled by diffusion through the CaSO 4 product layer. It must be remarked that, for the typical residence times of solids in FBC, the residual activity of the sorbent to the diffusion in the product layer was very important [15].…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The second one was slower and it can be controlled by diffusion through the CaSO 4 product layer. It must be remarked that, for the typical residence times of solids in FBC, the residual activity of the sorbent to the diffusion in the product layer was very important [15].…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] However, few works analyse the sulphation at oxy-fuel combustion conditions [19][20][21][22] and the major are related to non-calcining conditions. These studies found that the most important factors affecting to sulphur retention with Ca-based sorbents were temperature, CO 2 concentration, particle size and SO 2 concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2.44 shows that the wt.% capacity of the LC -based sorbent for CO 2 capture reduces from 58% in the fi rst cycle to 20% at the end of the 50th cycle caused by sintering or grain growth in the LC precursor in the course of cyclic reactions, rendering the structure susceptible to pore pluggage and pore mouth closure. 104,112,113 In contrast, it is shown in Figure 2.45 that the conversion of PCC -CaO during 100 cycles is distinctly higher than that of the LC -based sorbent. The capacity shown in Figure 2.45 is ∼ 68 wt.% in the fi rst cycle, which decreases to 40 wt.% in the 50th and slightly lower than 36 wt.% by the 100th cycle over ∼ 6,000 minutes on stream.…”
Section: Cyclic Calcination and Carbonation Behavior Of Ca -Based Sormentioning
confidence: 90%
“…Acid swelling is an experimental method for solving the incomplete conversion problem in the CaO reaction with SO 2 . It was proposed by Wu et al . The CaO sorbent was treated with acetic acid.…”
Section: Introductionmentioning
confidence: 99%